Overview of the Synthesis and Structure of Calix[n]quinones (n=4, 6, 8). Issue 19 (31st August 2020) - Hu, Pandeng; Cui, Huamin; Huang, Weiwei; Guo, Wenfeng
Abstract: Calix[n]quinones, a class of cyclic oligomers composed of p ‐benzoquinone structures connected by methylene, have multi‐conjugated carbonyl structures and adjustable cavities, which make their synthesis extremely attractive. In this minireview, synthetic methods of calix[n]quinones and recent synthetic experience of our group are summarized. The merits and demerits of various synthetic methods are briefly reviewed as well. When synthesizing calix[n]quinone (n≥6) with a larger ring, the reduction‐oxidation method is considered to be the most recommended. Abstract : Calix[n]quinones as organic cathode materials hold great potential in the field of ionic secondary batteries. This minireview provides a comprehensive review of the synthetic methods of calix[n]quinone (n=4, 6, 8) and highlights the reduction‐oxidation method.